mRNA expression of Somatostatin receptors 1-5 in MCF7 and MDA-MB231 breast cancer cells - Mahmoud, Alkhansa; Mancuso, María Teresa; Tanno, Barbara; Abu Bakar, Md Zuki; Hamzah, Hazilawati; Mohd Noor, Mohd Hezmee (Radiance Bahu - Uddeshiya Sanstha, 2021)
Background: Breast cancer is one of the most common types of cancer and heterogeneous disease. Somatostatin receptors (SSTRs) are expressed in normal and tumour tissues including breast cancer cells. Objective: The aim of this study to evaluate the expression of SSTRs subtypes 1 – 5 in MCF7 and MDA-MB231 human breast cancer cell lines and compare the levels between two cells. Methods: The detection of mRNA expression levels of SSTRs in MCF7 and MDA-MB231 was performed using quantitativepolymerase chain reaction (qPCR). Results: SSTR1, 2, 3 and 4 mRNA levels were significantly higher in MDA-MB-231 about MCF-7. The expression of SSTR 4 mRNA was highest in MDA-MB231 and MCF-7 cell lines, however, SSTR3 mRNA was least expressed in both cell lines. Conclusion: SSTRs subtypes (1 – 5) were expressed in both MDA-MB231 and MCF7 cells. However, the levels of expression differ between both cell lines.